Determinants of online shopping among tertiary students in Ghana: An extended technology acceptance model - Daniel Ofori; Christina Appiah-Nimo (Cogent Business & Management, 2019)
The increasing penetration rate of the internet and technology in the world is quickly promoting online shopping. This has been fueled by growing innovations in the telecommunication and financial sector in an attempt to depeen financial inclusion. Innovations such as mobile money payments systems by mobile telephony companies have contributed to the continuous growth in online shopping amidst and the new generation of consumers who desire richer experiences. This study sought to identify the determinants of online shopping behaviour among tertiary students through the lens of the Technology Acceptance Model (TAM). The study proposed a revised TAM that integrated perceived cost and perceived risk to investigate what determined students online shopping intention and actual use. The survey involved a sample of 580 undergraduate students. The statistical technique used was Structural Equation Modelling-Partial Least Squares (SEM-PLS). The results showed that effect of ease of use on usefulness was very significant as same has been predicted by the Technology Acceptance Model. Among the independent variables, perceived cost (PC) was found to be the most significant factor affecting actual use (AU) of online shopping among students, nonetheless, perceived cost (PC) had no significant effect on purchase intention (PI). Perceived risk (PR) had no significant effect on actual use (AU) however, had a significant effect on purchase intention (PI). The study recommends online sellers to make online shopping efficient and less costive with assured safety and security of transactions as well as the product itself. A set of shopping platform could even be created specifically to give discounts and other offers to students. It also recommends future studies to employ additional determining factors such as the type of product/service, convenience and personal/demographic and geographic factors as influential to students' online purchasing behaviour.
Keywords: 650; online shopping; purchase intentions; students; technology acceptance model